Detoxification of toxins by bacillithiol in Staphylococcus aureus - Newton, Gerald L. (Society for General Microbiology, 2012)
Bacillithiol (BSH), an α-anomeric glycoside of l-cysteinyl-d-glucosaminyl-l-malate, is a major low-molecular-mass thiol found in bacteria such as Bacillus sp., Staphylococcus aureus and Deinococcus radiodurans. Like other low-molecular-mass thiols such as glutathione and mycothiol, BSH is likely to be involved in protection against environmental toxins including thiol-reactive antibiotics. We report here a BSH-dependent detoxification mechanism in S. aureus. When S. aureus Newman strain was treated with monobromobimane and monochlorobimane, the cellular BSH was converted to the fluorescent S-conjugate BS-bimane. A bacillithiol conjugate amidase activity acted upon the BS-bimane to produce Cys-bimane, which was then acetylated by an N-acetyltransferase to generate N-acetyl-Cys-bimane, a mercapturic acid. An S. aureus mutant lacking BSH did not produce mercapturic acid when treated with monobromobimane and monochlorobimane, confirming the involvement of bacillithiol. Furthermore, treatment of S. aureus Newman with rifamycin, the parent compound of the first-line anti-tuberculosis drug, rifampicin, indicated that this thiol-reactive antibiotic is also detoxified in a BSH-dependent manner, since mercapturic acids of rifamycin were observed in the culture medium. These data indicate that toxins and thiol-reactive antibiotics are detoxified to less potent mercapturic acids in a BSH-dependent manner and then exported out of the cell in S. aureus.